2018
DOI: 10.1016/j.amepre.2018.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination Coverage Among English-Speaking Asian Americans

Abstract: Introduction: English-speaking non-Hispanic Asians (Asians) in the U.S. include populations with multiple geographic origins and ethnicities (e.g., Asian Indian, Chinese, Filipino, Japanese, Korean, and Vietnamese). Health behaviors and outcomes can differ widely among Asian ethnicities, and highlight the importance of subgroup analysis. Aggregating Asians may mask differences in influenza vaccination across various ethnicities. Methods: Combined data from 2013 to 2015 Behavioral Risk Factor Surveillance Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…Black and AIAN respondents were less likely than White respondents to receive the influenza vaccine. These findings are also congruent with the established literature [ 34 , 35 , 36 , 37 , 38 ]. Although NHPI respondents reported slightly lower vaccination uptake than White respondents, the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 93%
“…Black and AIAN respondents were less likely than White respondents to receive the influenza vaccine. These findings are also congruent with the established literature [ 34 , 35 , 36 , 37 , 38 ]. Although NHPI respondents reported slightly lower vaccination uptake than White respondents, the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 93%
“…When we look at each racial/ethnic minority group separately, startling low rates of influenza vaccination were found in 2017: 28.4% for Hispanic, 32.3% for non-Hispanic black, 33.1% for American Indian/Alaska native, 40.2% for non-Hispanic white, and 42% for Asian American adults (Centers for Disease Control and Prevention, 2018). This is similar to the data from the Behavioral Risk Factor Surveillance System for 2013–2015 (Srivastav et al, 2018). Even with the fact that none of the racial/ethnic groups could approach the average percentage on flu vaccination, not many prior studies have focused on identifying risk factors for low vaccination among Asian Americans.…”
Section: Introductionsupporting
confidence: 80%
“…The demographics associated with flu vaccination uptake in the US adult general population are well established – studies have found that race/ethnicity, age, sex, socio-economic-status (SES), insurance, having a usual source of care, contact with physicians, health behaviors, health status, and receipt of other vaccinations, and beliefs are associated with flu vaccine uptake ( Kamis et al, 2017 , Lu et al, 2015 , Schmid et al, 2017 , Takayama et al, 2012 , Williams et al, 2017 ). The majority of literature examining correlates of vaccine uptake compare racial ethnic groups to non-Hispanic (NH) whites ( Budhwani and De, 2016 , Hughes et al, 2019 , Lu et al, 2017 , Lu et al, 2015 , Srivastav et al, 2018 , Stafford et al, 2013 , Tse et al, 2018 ). The existing studies which examine flu vaccine uptake within specific US racial/ethnic groups are of limited generalizability due to the fact that they focus on the population of individual states or localities ( Bazargan et al, 2020 , Cohen et al, 2012 , Hughes et al, 2018 , Mendiola et al, 2016 , Moran et al, 2017 ), or specific adult subpopulations ( Bazargan et al, 2020 , Crouse Quinn et al, 2017 , Moran et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%